2013
DOI: 10.21236/ada584653
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Occupational Stress and Prevalence of Burnout and Clinical Distress Among U.S. Air Force Cyber Warfare Operators

Abstract: This report is published in the interest of scientific and technical information exchange, and its publication does not constitute the Government's approval or disapproval of its ideas or findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Such stressors are not unlike those faced by other USAF "virtual warriors" sustaining around-the-clock operations such as USAF image analysts and intelligence oper ators,12 as well as cyber warfare operations. 13 The results of their studies were consistent with an earlier study finding elevated levels of fatigue among USAF Predator drone opera tors having to sustain around-the-clock shift work. 14 The term "distress" is used to refer to an unpleasant state characterized by negative emotional (e.g., feelings of anger, agitation, sadness), behavioral (e.g., trouble getting along with others), physical (e.g., difficulty sleeping, fatigue, muscle tension, headaches), and cognitive (e.g., difficulty concentrat ing, sustaining attention) symptoms.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such stressors are not unlike those faced by other USAF "virtual warriors" sustaining around-the-clock operations such as USAF image analysts and intelligence oper ators,12 as well as cyber warfare operations. 13 The results of their studies were consistent with an earlier study finding elevated levels of fatigue among USAF Predator drone opera tors having to sustain around-the-clock shift work. 14 The term "distress" is used to refer to an unpleasant state characterized by negative emotional (e.g., feelings of anger, agitation, sadness), behavioral (e.g., trouble getting along with others), physical (e.g., difficulty sleeping, fatigue, muscle tension, headaches), and cognitive (e.g., difficulty concentrat ing, sustaining attention) symptoms.…”
Section: Introductionsupporting
confidence: 85%
“…The results of the study are similar to the occupational stressors reported by Predator/ Reaper drone operators in 2010,11 as well as other USAF "virtual warriors" sustaining around-the-clock intelligence exploitation12 and cyber warfare. 13 The repeated finding of operational stressors, as opposed to combat stressors, as the most problematic self-reported sources of stress is helpful for line commanders and medical personnel in developing inter ventions for mitigating stress and promoting performance. Although combat-related stressors were not reported to be a top source of occupational stress, such a finding is interpreted cautiously when evaluating an individual operator.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the Malasch Burnout Inventory suggest that burnout in this population was moderately high, with 30% of participants exceeding a sum score of 20 on one or more subscales. This proportion exceeds that observed for the general Air Force population (Chappelle et al, 2013) and is comparable with highly tasked intelligence and remotely piloted aircraft (RPA) operations units. In contrast to those units, burnout in our Security Forces sample was driven largely by cynicism as opposed to emotional exhaustion or concerns about professional efficacy; the proportions exceeding cutoff for those subscales were consistent with the general Air Force population at 15%.…”
Section: Burnoutmentioning
confidence: 71%
“…Due in large part to the small groups, there were no statistically significant differences in OQ45.2 score as a function of SRTS vs. standard intervention. If the proportion of enrolled participants is reflective of OQ-45.2 scores for the unit as a whole, there is some cause for concern regarding psychological well-being as the 29% rate is well above other Air Force populations, which range from 9-15% (Chappelle et al, 2013). Self-selection bias in choosing to participate in the study may have somewhat inflated this estimate.…”
Section: Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation